MIR337-3p Enhances Mycobacterial Pathogenicity Involving TLR4/MYD88 and STAT3 Signals, Impairing VDR Antimicrobial Response and Fast-Acting Immunity - Liang, Shanshan; Huang, Guixian; Wu, Tian; Peng, Ying; Liu, Xi; Ji, Xuejiao; Sha, Wei; Wang, Feifei; Shen, Ling; Shen, Hongbo (Frontiers in Immunology, 2021)
Active form of vitamin D (VitD) enhances human innate immunity against Mycobacterium tuberculosis (Mtb) infection. Our previous studies showed that MIR337-3p was highly expressed in lymphocytes of tuberculosis (TB) patients. Here, we identified the mechanism of MIR337-3p in the regulation of fast-acting anti-TB immunity by inhibiting VitD-dependent antimicrobial response pathways. While high-level MIR337-3p expression was induced by mycobacterial infection in cellular models and mice, TB patients exhibited significantly increased MIR337-3p in CD14+ monocytes/macrophages, innate-like Vγ2+ T cells, and CD8+ lymphocytes containing natural killer (NK)/innate lymphoid cells. MIR337-3p promoted the mycobacterial entry/infection and replication/growth in host target cells: macrophages and lung epithelial cells. Such MIR337-3p-enhanced pathogenicity coincided with the MIR337-3p depression of VitD-dependent antimicrobial response of cytochrome P450, family 27, subfamily b, polypeptide 1 (CYP27B1)/Beta-defensin 4 (DEFB4A)/ cathelicidin antimicrobial peptide CAMP pathways. Surprisingly, single MIR337-3p species could specifically target both the Toll-like receptor 4 (TLR4) and signal transducer and activator of transcription 3 (STAT3) 3′-untranslated regions (UTRs) to depress the TLR4/MYD88 and STAT3 signals and impair either of the two signals inhibiting the VitD-dependent antimicrobial pathways in macrophages. Concurrently, human peripheral blood mononuclear cells (PBMCs) expressing high-level MIR337-3p exhibited a reduced ability of innate cell populations to mount fast-acting cellular immunity against intracellular mycobacterial infection. Furthermore, a higher expression of Mir337-3p after mycobacterial infection of mice coincided with much greater colony-forming unit (CFU) counts in lungs and even the death of infected animals, whereas Mir337-3p inhibitor treatment of infected mice reduced Mir337-3p levels and reversed Mir337-3p-mediated increases in CFU counts. Thus, TB-driven single MIR337-3p species could specifically target/impair both TLR4/MYD88 and STAT3 activation signals, inhibiting VitD-dependent antimicrobial response and fast-acting anti-TB immunity, leading to enhanced pathogenicity.